2009
DOI: 10.1002/path.2531
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol depletion induces anoikis‐like apoptosis via FAK down‐regulation and caveolae internalization

Abstract: Caveolae (lipid rafts), microdomains of the plasma membrane, are known to contain various signalling molecules and consequently are involved in the regulation of many biological functions. To investigate the role of the caveolae in cell survival and adhesion, we disrupted the caveolae by depletion of cholesterol, a major lipid component of the caveolae, with methyl-beta cyclodextrin (MbetaCD) treatment of A431 cells. We found that cholesterol depletion induced an anoikis-like cell death involving actin reorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 54 publications
10
48
0
1
Order By: Relevance
“…As stated under Results and in accordance with reports by other authors using different cells lines (Li et al, 2006;Park et al, 2009), the exposure of HepG2 cells to 5 mM M␤CD significantly depletes their cholesterol content and at the same time causes them to become round in shape. These changes are reversed by cholesterol replenishment.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…As stated under Results and in accordance with reports by other authors using different cells lines (Li et al, 2006;Park et al, 2009), the exposure of HepG2 cells to 5 mM M␤CD significantly depletes their cholesterol content and at the same time causes them to become round in shape. These changes are reversed by cholesterol replenishment.…”
supporting
confidence: 78%
“…Because cholesterol is an essential lipid component of the rafts involved in Akt activation and, as we have demonstrated here, cholesterol is depleted by exposure to APLs, we looked to see whether changes in plasma-membrane cholesterol levels altered the activation state of Akt. We used M␤CD as a positive control and found that incubation with M␤CD decreased the phosphorylation of Akt and that, after replenishment with cholesterol, the levels of phosphorylated Akt returned to control values, all of which are in accordance with data reported in other cell lines after treatment with cyclodextrins (Park et al, 2009). Likewise, the depletion of cholesterol produced after exposure to APLs led to a reduction of Akt phosphorylation in HepG2 cells, suggesting that APLs may act on Akt via the depletion of plasma-membrane cholesterol.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…In this respect, it has been demonstrated that cholera toxin B subunit in association with its receptor, GM1, can be internalized via caveolae/rafts [48] and that MbCD may remove gangliosides, although this is related to high MbCD concentrations [65]. In addition, disruption of caveolae by MbCD led to the mobilization of GM1 and caveolin-1 from the plasma membrane to the cytoplasm in A431 cells [66].…”
Section: Discussionmentioning
confidence: 98%